2021
DOI: 10.12973/ejmse.2.1.47
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Examination of the Impacts and Lessons Learned from a Professional Development Program for Out-of-Field Mathematics Teachers

Abstract: <p style="text-align:justify">As international concerns about the prevalence of out-of-field teaching have grown, so have discussions about how to support out-of-field teachers. In Ireland, the Professional Diploma in Mathematics for Teaching, a two-year professional development program, was created for out-of-field mathematics teachers. A pre-test, post-test, and final survey examined the program’s impact on participating teachers’ mathematical knowledge, confidence in teaching curricular content, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Most of the participants emphasized that partnership and cooperation in the community is expressed by understanding the mutual needs of each of the partners and making joint decisions. Regarding personal traits and inner knowledge of the participants, the findings are in line with those of (Paolucci et al, 2021), who found that increases in teachers' mathematical knowledge and self-efficacy along with self-reported impact on practice are positive outcomes. This is similar to what has been reported by (Avidov-Ungar, 2017;Cary, 2002) that in learning communities it turns out that there is significant collaboration and collaborative learning in the social context, which enriches all group members in terms of positivity, confidence and accumulative knowledge.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Most of the participants emphasized that partnership and cooperation in the community is expressed by understanding the mutual needs of each of the partners and making joint decisions. Regarding personal traits and inner knowledge of the participants, the findings are in line with those of (Paolucci et al, 2021), who found that increases in teachers' mathematical knowledge and self-efficacy along with self-reported impact on practice are positive outcomes. This is similar to what has been reported by (Avidov-Ungar, 2017;Cary, 2002) that in learning communities it turns out that there is significant collaboration and collaborative learning in the social context, which enriches all group members in terms of positivity, confidence and accumulative knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…However, results regarding their effectiveness have been inconsistent (Prenger et al, 2018). Besides, identifying specific content areas for which weaknesses in the teachers' knowledge persisted is important for the improvement of this particular professional development program (Paolucci et al, 2021). Today, many countries adopt the model due to various incentives that shape the characters and goals of the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation